Electromyographical activity of the pectoralis, triceps, and deltoideus during the sub-phases of bench press in paralympic powerlifters - da Silva, B. G.; Miziara, I. M.; Furtado, D. A.; dos Santos, S. S.; Fidale, T. M., Pereira, A. A. (Sports Engineering, 2022)
High-performance training program development has benefitted from studies of the mechanisms involved in performing the bench press. This study aimed to analyze the electromyographic and kinematic parameters affecting high-performance athletes during the phases of the Paralympic bench press movement. The root mean square, mean frequency, and frequency median variables were analyzed for the pectoralis major, triceps brachii, and anterior deltoideus. Four females aged 23 to 48years (mean 39.8 ± 11.2) and six males aged 18 to 41years (mean 26.5 ± 8.0) performed three attempts at 95% of their dynamic maximum voluntary contraction load, obeying the rules of the modality. For all movement sub-phases, the pectoralis major and deltoideus root-mean-square values indicated greater activation (level of significance of. ? = 0.05). The triceps brachii presented high values of the frequency domain variables, especially in the concentric phase of the bench press movement, suggesting a firing rate higher than the other muscles studied. Therefore, the triceps muscle must be trained effectively, especially to assist in the concentric phase and the sticking sub-phase. These results suggest that resistance-training programs should include variations in bench press format to optimize the force output during different sub-phases.